2001
DOI: 10.1007/s00167-001-0258-7
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopy, assisted percutaneous repair of the Achilles tendon ruptures: a cadaveric and clinical study

Abstract: Endoscopy-assisted percutaneous repair of Achilles tendon ruptures were investigated in a cadaveric and clinical study. Sixteen above-knee fresh amputation specimens in which different types of Achilles tendon ruptures were created were repaired percutaneously with the visualization of the tendon ends by endoscopy. Neither malalignment nor damage to the neurovascular structures was observed. Eleven patients were treated in this way. No reruptures, wound problems, or neurovascular injury were observed. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…7-10 Lui described the treatment of chronic non-insertional Achilles tendinopathy with endoscopic Achilles debridement and flexor hallucis longus transfer. 11 Gossage et al reported the endoscopic assistance for the augmentation of a chronic Achilles tendon rupture with flexor hallucis longus tendon.…”
Section: Resultsmentioning
confidence: 99%
“…7-10 Lui described the treatment of chronic non-insertional Achilles tendinopathy with endoscopic Achilles debridement and flexor hallucis longus transfer. 11 Gossage et al reported the endoscopic assistance for the augmentation of a chronic Achilles tendon rupture with flexor hallucis longus tendon.…”
Section: Resultsmentioning
confidence: 99%
“…Turgut investigated the use of endoscopically assisted Achilles repairs using a Ma-Griffith construct in 16 specimens and reported success in a series of 11 patients without complications [57]. The average return to daily activities was 10-11 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…This development led to the use of a mini-incision with a jig for needle passage and other entirely percutaneous techniques [55,56]. The use of endoscopy was described as an adjunct to the percutaneous repair and allows an evaluation of the tendon quality, debridement and mobilization of tendon ends, accurate passage of needles, and guided approximation of the tendon ends [57][58][59][60][61][62].…”
Section: Achilles Tendon Rupturementioning
confidence: 99%
“…Many surgeons have advocated a number of modifications to the percutaneous or minimally invasive techniques, each with its own advantages and disadvantages. 2,11,[24][25][26][27] The minimally invasive technique described here using a double-ended needle is simple and easily mastered with a short learning curve. It is technically less demanding than a standard open repair.…”
Section: Discussionmentioning
confidence: 99%